The Role of Mediation of Customer Satisfaction on The Relationship of Service Quality With Customer Loyalty at Villa Lebak Bali Residence - Wardana, I Made Aditya (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
Quality of service is the level of excellence that the customer expects. If the service received or felt is as expected, the service quality is said to be good and satisfying. This study aims to reexamine the mediating role of customer satisfaction on the relationship of service quality with customer loyalty. Service quality (X1) as the independent variable, customer satisfaction (Y1) as a mediating variable and customer loyalty (Y2) as the dependent variable The type of research used is explanatory research. The research location was in Villa Lebak Bali Residence, Canggu, North Kuta. The study population was customers who stayed at Villa Lebak Bali Residence. Samples of 96 respondents were taken using purposive sampling techniques and dataacollection methods using questionnaires. Analysis of the dataaused is descriptive analysis, and PLS. The results showed that the service quality variable significantly influenced the satisfaction variable with a significant value of 0.677. Service Quality Variable has no significant effect on the Loyalty variable with a value of 0.191. The satisfaction variable has a significant effect on the loyalty variable with a significant value of 0.478 and the satisfaction variable mediates the quality of service to loyalty is significant with the coefficient value of indirect effects 0.324. Further research can add variables related to service quality, customer satisfaction and customer loyalty.